COVID-19 in a rural health system in New York - case series and an approach to management - Eyal Kedar; Regina Scott; Daniel Soule; Carly Lovelett; Kyle Tower; Kylie Broughal; Daniel Jaremczuk; Sara Mohaddes; Imre Rainey-Spence; Timothy Atkinson (James Cook University, 2021)
Introduction: Many rural hospitals and health systems in the USA lack sufficient resources to treat COVID-19. St Lawrence Health (SLH) developed a system for managing inpatient COVID-19 hospital admissions in St Lawrence County, an underserved rural county that is the largest county in New York State. Methods: SLH used a hub-and-spoke system to route COVID-19 patients to its flagship hospital. It further assembled a small clinical team to manage admitted COVID-19 patients and to stay abreast of a quickly changing body of literature and standard of care. A review of clinical data was completed for patients who were treated by SLH's inpatient COVID-19 treatment team between 20 March and 22 May 2020. Results: Twenty COVID-19 patients were identified. Sixteen patients (80%) met National Institutes of Health criteria for severe or critical disease. One patient died. No patients were transferred to other hospitals. Conclusion: During the first 2 months of the pandemic, the authors were able to manage hospitalized COVID-19 patients in their rural community. Development of similar treatment models in other rural areas should be considered.